2016
DOI: 10.1515/acph-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatography for simultaneous determination of xipamide, triamterene and hydrochlorothiazide in bulk drug samples and dosage forms

Abstract: A novel, simple and robust high-performance liquid chromatography (HPLC) method was developed and validated for simultaneous determination of xipamide (XIP), triamterene (TRI) and hydrochlorothiazide (HCT) in their bulk powders and dosage forms. Chromatographic separation was carried out in less than two minutes. The separation was performed on a RP C-18 stationary phase with an isocratic elution system consisting of 0.03 mol L -1 orthophosphoric acid (pH 2.3) and acetonitrile (ACN) as the mobile phase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Green color symbolizes low ecological impact, while yellow and red colors represent higher impacts. GAPI was used to compare the proposed method to the other reported methods [18,19] ( Fig. 3).…”
Section: Evaluation Of the Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Green color symbolizes low ecological impact, while yellow and red colors represent higher impacts. GAPI was used to compare the proposed method to the other reported methods [18,19] ( Fig. 3).…”
Section: Evaluation Of the Analytical Proceduresmentioning
confidence: 99%
“…So, the elution time of our drugs under study was quite longer. Only three methods were reported focusing on determination of the drugs under study using HPLC-UV detection [17][18][19]. Two of those methods have the disadvantage of using gradient technique with run time exceeding 12 min.…”
Section: Introductionmentioning
confidence: 99%
“…It has a relatively inefficient effect for treatment of antihypertensive when used alone; so it is used in combination with a potent diuretic (e.g. anthranilic acid or thiazide derivative) to give a synergistic action [8]. Hydrochlorothiazide is 6-chloro-3,4-dihydro-2H-1,2,4-benzothiadiazine-7-sulfonamide-1,1-dioxide is a thiazide class diuretic.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review shows that triamterene and hydrochlorothiazide were determined in their bulk powder by derivative ratio spectrophotometry [10] and liquid chromatography [8]. The aim of this work is to develop and validate a new analytical method for determination of the tertiary mixture triamterene and hydrochlorothiazide in presence of impurity of hydrochlorothiazide (chlorothiazide) as well as determination of spironolactone and furosemide in presence of impurity of furosemide (anthranilic acid) in bulk powder and pharmaceutical dosage form without interference or prior separation.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature revealed that many analytical methods have been developed for the assay of XIP including: spectrophotometry, spectrofluorimetry, high‐performance liquid chromatography (HPLC), thin‐layer chromatography–densitometry and electrochemical methods…”
Section: Introductionmentioning
confidence: 99%